Evaluating the feasibility and preliminary effects of an online compassion training program for nursing students: A pilot randomized controlled trial - Zhi Yang; Mimi Mun Yee Tse; Huiting Huang; Haiyun Fang; Joanne Wai Yee Chung; Doris Yin Kei Chong; Thomas Kwok Shing Wong (Elsevier, 2024)
Objectives: This study aimed to assess the feasibility of an online compassion training program for nursing students and preliminarily investigate its effects on mindfulness, self-compassion, and stress reduction. Methods: This study employed a randomized controlled trial design. Second-year students from a nursing college in Guangzhou, China, were recruited as research participants in August 2023. The intervention group participated in an 8-week online compassion training program via the WeChat platform, comprising three stages: mindfulness (weeks 1-2), self-compassion (weeks 3-5), and compassion for others (weeks 6-8). Each stage included four activities: psychoeducation, mindfulness practice, weekly diary, and emotional support. Program feasibility was assessed through recruitment and retention rates, program engagement, and participant acceptability. Program effectiveness was measured with the Mindful Attention Awareness Scale, Self-Compassion Scale - Short Form, and Perceived Stress Scale. Results: A total of 28 students completed the study (13 in the intervention group, 15 in the control group). The recruitment rate was 36.46%, with a high retention rate of 93.3%. Participants demonstrated high engagement: 69.2% accessed learning materials every 1-2 days, 93.3% practiced mindfulness at least weekly, with an average of 4.69 diary entries submitted per person and 23.30 WeChat interactions with instructors. Regarding acceptability, all participants expressed satisfaction with the program, with 92.4% finding it "very helpful" or "extremely helpful." In terms of intervention effects, the intervention group showed a significant increase in mindfulness levels from pre-intervention (51.54 ± 10.93) to post-intervention (62.46 ± 13.58) (P < 0.05), while no significant change was observed in the control group. Although there were no statistically significant differences between the two groups in post-intervention self-compassion and perceived stress levels, the intervention group showed positive trends: self-compassion levels increased (35.85 ± 8.60 vs. 40.85 ± 5.54), and perceived stress levels slightly decreased (44.77 ± 8.65 vs. 42.00 ± 5.77). Conclusions: This pilot study demonstrated the feasibility of an online compassion training program for nursing students and suggested its potential effectiveness in enhancing mindfulness, self-compassion, and stress reduction. Despite limitations such as small sample size and lack of long-term follow-up, preliminary evidence indicates promising prospects for integrating such training into nursing education. Further research is warranted to confirm these findings and assess the sustained impact of this approach on nursing education and practice.